Oxford book of poetry for children - Blishen, Edward, 1920-; Wildsmith, Brian (New York : Watts, 1963)
An anthology of English poetry intended to introduce children beyond the nursery rhyme level to serious verse--Publisher's note.
Includes index.
6.5
Keywords: Children's poetry, English; English poetry -- Collections; English poetry -- Collections